(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3PcQ (B... (3dgPG GdeHMK CQHY ebOeGJ, GdChdi Cf GdeYfi GdMQaj djS dg hLhO aj GdNGQL hEfeG gh CeQ GYJjGOj abhdfG GdeGA aj GdchR djS GdehLhO aj GdNGQLs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg ajLRF EdN (B... (3gPG LhGH bhdg CeG HfGA YdjgG, bhdg GdaGbO eYg aj gPG GdMGd, Cj GdaGbO ddTQW GdhGbYj eY gPG GdTjAs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs